FULL ASSESSMENT OF RADIATION THERAPY RESULTS OF DIFFERENT FRACTIONATION REGIMES CHEMOMODIFICATION AMONG III STAGE NON-SMALL-CELL LUNG CANCER PATIENTS - Starenkiy, V. P.; Sukhina, O. M.; Bielozor, M. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The analysis of the results of radiation therapy (RT) using different fractionation regimes among 82 patients with IIIA and IIIB stage non-small-cell lung cancer (NSCLC) was held. All of the patients were divided into three groups: the first one (consisted of 30 patients) – standard RT; the second one (consisted of 27 patients) – accelerated hyperfractionated RT; the third one (consisted of 25 patients) – RT using an accelerated regime with the dose escalation and etoposide chemomodification. There was an overt effect observed in the groups 2 and 3 (74,1±8,6% and 72±9,2% in the groups 2 and 3 respectively against 40±8,9% in the group 1 p<0,05). In this groups high annual survival rate is observed (66,7±9,2% and 64±9,8% respectively against 43,3±9,0% in the group 1 p>0.05). However, early I-II grade radiation pneumonitis were observed rarer in the groups 1 (16,7±6,8%) in comparison with the groups 2 and 3 (37±9,5% and 36±9,8% respectively). Patient’s life quality improvement was observed in all of the groups, however, clinical effect comes in 2-3 weeks earlier in case of an accelerated RT administration. Late radiation changes of pulmonary tissues exercise a significant negative influence on life quality of NSCLC patients after the RT had been held for the period of 3 to 8 months of observation as a result symptomatic therapy is to be administered during the stages of RT and follow-up care.